Analisis Kinerja Kondensor Sebelum Dan Sesudah Overhoul Di PT. Indonesia Power UJP PLTU Lontar Banten Unit 3 - Prayudi Prayudi; Sudirmanto Sudirmanto; Dimas Indra Wijaya (JURNAL POWERPLANT, 2016)
In this paper, described the condenser kinerjance analysis before and after overhoul. Plant is used as object of research is power plant PT. Indonesia Power UJB Lontar Banten Unit 3. The power plant consists of three units, the capasity each of 315 MW. Power plant Lontar Banten works by using cycle rankine. Condensers used are surface condenser, where the steam and cooling water separately. The efficiency of the condenser is affected by the value of heat rate, heat condenser, a decrease in the average logarithmic temperature, cleanliness factor. Condenser heat is calculated by heat balance approach and condenser heat rejection. The data used in this study is data operations in 2015 (Juni 2015 and Oktober 2015). From the analysis of the obtained results that the increased efficiency of the condenser by 10% from 43.6% to 53.6% after the overhoul. Increasing the efficiency of the condenser is affected by the decrease in heat rate 5.32 %, decrease condenser heat 7.03 %, decrease the average temperature logarithmic 8.11 %, improved cleanliness factor of 22.91 %. From these results indicate that the activity overhoul effectively improve the efficiency of the condenser